Classification of the necessary tests of convergence in the theory of numerical series - Mironenko, L.P.; Petrenko, I.V.; Vlasenko, A.Yu. (Искусственный интеллект, 2013)
The paper suggests three types of the necessary tests for the convergence of numerical series with positive terms. It is shown that these tests are consequences of the limit test of comparison with respect to the standard series: harmonic and logarithmic ones. The new tests have different capabilities and can be applied to almost any series, whose terms form a monotone sequence.